DATASUS and the challenges in the collection and dissemination of health information for the black population - Gomes, Maria Cristina; Cruz, Aline de Jesus (Seven Editora, 2023)
Health information with a racial cut is a relevant instrument for the planning of actions and interventions to combat social inequalities. Such information was indispensable for the formulation of the National Policy for the Integral Health of the Black Population. However, these data do not yet present a completeness that allows analyzing the entire trajectory of the citizen in the health services at the municipal level. The article aims to present the difficulties of access and the gaps of completeness of the DATASUS data in the municipality of Camaçari, and to present a reflection on how these gaps hinder the estimation, dissemination, and application of indicators with racial focus for the follow-up and evaluation of inclusive health policies. Through quantitative methodology, an analysis of the available data on the use of health services with racial cuts, using the tabnet and tabwin systems, was carried out. It is demonstrated that most of the records ignore the question about the race-color of the users; The few who present it are insufficient to make a complete and reliable diagnosis. DOI:https://doi.org/10.56238/innovhealthknow-031